Determination of citrat ions in drugs on molecular luminescence of rutine in complex with yttrium (III) - S. V. Beltyukova; O. V. Malynka; O. O. Livencova (Фармацевтичний журнал, 2019)
The development of methods for qualitative and quantitative analysis of drugs can guarantee their identity and quality. Drugs used in the form of salts of organic bases are often determined by the anionic part of these salts. Citrate ions are a part of many drugs in the form of citric acid, salts of alkaline and alkaline earth metals.